Estudos de sistemas supramoleculares à base de ciclodextrinas e nanofibras de polímeros biodegradáveis para a liberação controlada de fármacos - Michele Fabiane de Oliveira (2015)
In this work supramolecular system involving -cyclodextrin and drug delivery systems of hydrophilic drugs based on polymer nanofibers containaing poly--cyclodextrin combined with other biocompatible polymers were obtained. Initially, the formation of inclusion compound between propranolol hydrochloride, an antihypertensive drug, and -cyclodextrin was studied in solution, as well as its self-assembly process. These nanoaggregates possess sizes ranging from 220 to 300 nm. The thermodynamic parameters of nanoaggregates formation showed a spontaneous and temperature dependent process. The stoichiometric coefficients increase with temperature rise reaching structural arrangements consisting of 4:1 (propranolol hydrochloride:-cyclodextrin) at 318.15 K. The second delivery system obtained using propranolol hydrochloride were uniaxial and coaxial polymeric nanofibers based on -cyclodextrin polymer (poliCD) and PMAA. Their structural, thermal and morfological properties were evaluated seeking to establish correlations of physical-chemical and biological structure-property. These two fiber arrangements have a direct influence in drug release. The burst effect was dramatically modulated into the coaxial fibers, 44 % lower than uniaxial fibers in 8 h. Thus, the coaxial arrangement is an alternative strategy for the release of propranolol hydrochloride. The third delivery system developed were the uniaxial polymeric nanofibers based on PLGA containing the daunorubicin hydrochloride, chemotherapy for clinical use. The burst effect of about 65 % of the amount of drug present in the fiber at 8 h was observed followed by a slow and gradual release of the drug. The in vitro results have shown that the nanofibers containing daunorubicin hydrochloride showed higher cytotoxic effect against A431 tumor cells when compared to the free drug. In vivo experiments revealed that the nanofibers containing the drug showed greater anti-angiogenic effect, with reduced vasculature and not showing inflammatory potential, suggesting an alternative system for release of daunorubicin.